Aprendendo com tarefas: jogo sério para auxílio na alfabetização de crianças com deficiência intelectual - Vasconcelos, Daniel Felipe Pereira de (2018)
In a context of growth of the serious games’ development for the Education area, there is still a low number of games aimed at people with Intellectual Disability. Considering the potential of Virtual Reality (VR) as a technology to support the different areas of knowledge, this work aimed to develop a serious game using VR technology to serve as a tool to support the literacy of children with Intellectual Disability, called Aprendendo com Tarefas. For this, at first, a protocol was created with requirements and specifications of a serious game to support the teaching of writing, reading and speaking of everyday objects’ name and the game environment, which was validated together with professionals of the Education area who work in Specialized Educational Assistance (AEE). Later, the game Aprendendo com Tarefas was developed from this protocol. To evaluate the game as apt to be a tool to support the literacy process of children with Intellectual Disability, the qualitative evaluation methodology was adopted. Two questionnaires were applied to three teachers from two primary municipal schools of Uberlândia/MG city, who used the game with eight children. The first questionnaire about the teachers themselves, with two sets of questions: the first with data related to educational background and experience with the AEE and the second with questions about the perceptions of the game, recording the evaluations and the facts that occurred during the game’s play with the children. The second questionnaire about the children who used the game, with three sets of questions: the first one about the student data, the second about his/her profile, and the third about the student's aspects related to literacy. The results of the qualitative evaluation were positive and indicated the game as a valid tool to support the literacy process of children with Intellectual Disability.